Evolutionary and biogeographic relationships of related Ranunculus taxa: dispersal, vicariance and pseudovicariance as mechanisms of change. (2nd November 2017) - Fernández Prieto, José Antonio; Sanna, Mauro; Pérez, Marta; Pérez-Haase, Aaron; Molero-Mesa, Joaquín; Cires, Eduardo
Abstract : Background : The disjunct distribution patterns of a taxon may arise when previously continuous distribution ranges are fragmented. The phenomena of vicariance and dispersal, together with hybridisation as an important source of genetic variation in natural populations, can play an important role for structuring the distribution of taxa. Aims : We investigated the biogeographical relationships of the Iberian endemic plant Ranunculus angustifolius s.l . by reconstructing ancestral geographical distributions, using a combination of phylogenetic and distributional information. Methods : Phylogenetic and network analyses of nuclear internal transcribed spacers and plastid sequence data ( rpl32-trnL, rps16-trnQ, trnK-matK and ycf6-psbM ) were used to infer vicariance and dispersal events. Results : Phylogenetic and biogeographical analyses suggested that both dispersal and vicariance were important in creating the current disjunct distribution pattern. Some other factors, such as hybridisation, introgression and vicariance (or pseudovicariance), were important in the evolutionary history of the taxa R . angustifolius s.l. Conclusions : Our results demonstrate the importance for analysing biogeographical patterns with the use of both nuclear and chloroplast DNA to infer the evolutionary history of plant species with a disjunct distribution. Our results show that phenomena such as dispersal, vicariance and pseudovicariance are not mutually exclusive.